Exposing the Colonial Mind: Epistemologies of Ignorance and Education in Ontario, Canada - Schaefli, Laura (2018)
This dissertation weaves Indigenous and decolonial scholarship together with recent work on ignorance to consider the constraints and possibilities of decolonizing education in the current Canadian context of reconciliation. While the study of knowledge and its nature has been the focus of Western thought since ancient times, it is only recently that scholars have begun to grapple with ignorance as a social and political phenomenon in its own right. Ignorance, as these scholars use the term, is not a neutral or incidental absence of knowledge, waiting to be filled. Rather, it is epistemological, a powerful organizing logic that emerges from and works to sustain strategic methods of not knowing that, consciously or not, function to perpetuate the status quo, privilege, and domination. Ignorance in this sense is deeply tied to settler colonialism. To survive as a political and economic system, settler colonialism requires normalization of the ways of thinking that legitimate denigration and subjugation of Indigenous nationhoods. This dissertation elucidates the role of formal education in Ontario, Canada’s most populous province, in encouraging the formation of political subjects with deep, and often unacknowledged, investments in the maintenance of settler colonial relations of power. My colleagues and I worked with over 200 Indigenous educators to develop a research tool that seeks to assess how Ontario high school graduates are learning to think about colonialism and its relationship to First Nations, Métis and Inuit people(s) and Canadian society. This co-designed questionnaire was then disseminated to the first-year cohorts at 10 Ontario universities (over 42,000 students). Results from this study, together with findings from analysis of the most recent generation of Ontario K-12 curricula and textbooks, demonstrate the endurance of colonial modes of thought and their role in undermining the epistemological and affective orientations necessary for the development of decolonizing relations. I argue the ...